Diagnostic and environmental study of Aspergillus terreus isolated from various varieties of apples fruits - Khadega Hamza Kadhim; Ibtihal Muiz Al-Hussaini (Journal of Contemporary Medical Sciences, 2016)
Objectives This study includes the fungi isolated from apple fruits and diagnosis study with ecological factors for Aspergillus terreus. Methods The samples were collected from apple varieties which included red importer apples, red local apples, golden yellow importer apples, green importer apples. The collected apples had some obvious lesion or spoilage and isolated number of fungi that differences in appearance percent and used two primers SEQ ID NO and ITS for A. terreus diagnosis by using PCR technique; in addition the study includes using three factors effective on fungal growth with temperature 15, 20, 25, 30 and 35 C° with pH 4, 6, 8, 10 and 12 and the third factor culture medium PDA, SDA, CZA and MEA. Results Results revealed the presence of nine types of fungi which includes P. expansum, Rhizopus solonifer, Alternaria spp, A. flavus, A. niger, A. terreus, P. digitatum, P. italicum and yeast isolated from various apple fruits. Number of isolates P. expansum more than other fungi while less number was found in Rhizopus stolonifer. The A. terreus identified by amplicon size of that appear 100 bp for six isolates and it appears that four isolates carrying this gene has size of 600 base pairs. This study showed significant differences (p < 0.05) in effect of five temperatures 15, 20, 25, 30 and 35°C in the growth of fungus A. terreus and pH levels on growth on three isolates of genus the types of culture media (PDA, SDA, CDA, MEA) significant at p < 0.05 affected the growth of A. terreus and it had different morphological characteristics. Conclusion Number of fungi was found in apple and identified A. terreus by PCR method and studied different ecology factors on growth fungus. The best degree for the growth of isolates in the sixth day was 30°C. Maximum level of growth of the A. terreus was at pH 6 for all isolates in the sixth day and the growth rate for the same day on SDA reached 7.13 cm which was considered the best media for growth.